How to succeed as a scientist from postdoc to professor - Gabrys, Barbara J.; Langdale, Jane A. (Cambridge New York Cambridge University Press, 2011)
"This unique, practical guide for postdoctoral researchers and graduate students explains how to build and perfect the necessary research tools and working skills to build a career in academia and beyond. It is based on successful training workshops run by the authors: first, it describes the tools needed for independent research, from writing papers to applying for academic jobs; it then introduces skills to thrive in a new job, including managing and interacting with others, designing a taught course and giving a good lecture; and it concludes with a section on managing your career, from how to manage stress to understanding the higher education system. Packed with helpful features encouraging readers to apply the theory to their individual situation, the book is also illustrated throughout with real-world case studies to enable readers to learn from others' experience. It is a vital handbook for everyone seeking to make a successful scientific career --Provided by publisher
Becoming an independent researcher: managing your time. Giving a good research talk -- Writing a quality research paper -- Handling scientific criticism -- Writing grant applications -- Tools for managing research projects -- Is there life beyond academia? -- Applying for a job in academia -- Applying for an independent research fellowship -- Thriving in your new Job: handling new roles. Learning from other people -- Managing people -- Building a research group 1: doctoral students -- Building a research group 2: recruiting and supervising postdocs -- Interacting with others -- Designing a taught course -- Giving a good lecture -- Beyond lecturing -- Mentoring -- Managing your career: managing stress. Taking on new challenges -- The higher education system
Title from title screen (viewed November 3, 2023)
Electronic reproduction
Keywords: Science -- Vocational guidance